Disintegrative activation of Pd nanoparticles on carbon nanotubes for catalytic phenol hydrogenation. Issue 4 (25th January 2016) - Zhang, Liyun; Wang, Bolun; Ding, Yuxiao; Wen, Guodong; Hamid, Sharifah Bee Abd; Su, Dangsheng
Abstract : Inactive annealed Pd NPs can be disintegratively re-dispersed and re-activated through a HNO3 vapour treatment for enhanced catalytic phenol hydrogenation. Abstract : The strong dependence of catalytic activity and selectivity on the size of nanoparticles has imposed great value on facile methods for tailoring metal nanoparticles (NPs) with uniform dispersion on a heterogeneous support. Here, a simple and effective method for re-activating sintered Pd NPs decorated on carbon supports is demonstrated using HNO3 vapour at mild temperatures in a closed system, without loss in the Pd content. We further reveal that nitrogen oxide play an important role in the re-dispersion of Pd NPs. In a catalytic phenol hydrogenation reaction, the re-dispersed NPs exhibit superior catalytic activity as compared to sintered Pd NPs supported on CNTs.